An Overview: Auditing of Water Use on Construction Site: Addressing Water Use and Management on Construction Sites (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Water is essential for the living beings. The construction of cities in arid regions impedes imbalances between supply and demand. The water supplied by private supplier for construction purposes is not mentioned. That is why Innovative technology has been developed to support effective delivery called as water audit. In the late 1980s, water audits were conducted to overcome drought-related problems, scarcity, leaks, and losses. Water Audit provides a rational, scientific framework that categorizes the total water consumption in the system. The water audit is carried out mainly for the water that is not detected. The water audit helps to identify and quantify the additional water consumption and losses. The International Water Association (IWA) American Water Work Association (AWWA) have commenced a massive effort to mitigate related issues with the help of audits.